IMPACT OF SRI ORGANIC AS COMMUNITY DEVELOPMENT PROGRAM OF PT MEDCO E&P INDONESIA - Lita Ayudia Fitriyani; Yuni Ros Bangun (School of Business, Bogor Agricultural University (SB-IPB), 2014)
Indonesia is an agricultural country that has majority occupation as farmer. Unfortunately, farmers still become the biggest contributor to poverty in Indonesia around 62.25% in 2012. As a country that has a vision to become an independent country, Indonesia should be able to meet the welfare of its people, including farmers. This can be achieved if the cooperation between the government and the perpetrators of activities in Indonesia; such as natural resource companies that perform social responsibility programs as a contribution to society. One form of social responsibility is a community development program which is considered to be more useful. System of Rice Intensification or SRI Organic Organic is one of the community development programs that were developed to improve the welfare of farmers. The aim of this study were 1) to evaluate the impact of a given Organic SRI as a community development programs; 2) measuring the level of Organic SRI farmers' income; 3) Organic SRI analyze opportunities in the future as an independent and sustainable program. By doing a case study on community development programs conducted by PT Medco E & P Indonesia in the dusun parit 9, Banyuasin District, the authors analyze and evaluate the impact of using SEAGA to 20 respondents. The results of these studies are intended to provide input in order to make the community development program more effective in the future.Keywords: welfare, corporate social responsibility, community development, SRI organic, SEAGAABSTRAKIndonesia adalah negara agraris dimana petani merupakan mayoritas pekerjaan namun menjadi penyumbang kemiskinan terbesar di Indonesia sekitar 62,25% pada 2012. Sebagai negara yang memiliki visi untuk menjadi negara mandiri, Indonesia harus mampu memenuhi kesejahteraan rakyatnya termasuk petani. Hal tersebut dapat tercapai jika adanya kerjasama antara pemerintah dan pelaku aktivitas di Indonesia; seperti perusahaan sumber daya alam yang melakukan program tanggung jawab sosial sebagai kontribusi untuk masyarakat. Salah satu bentuk dari tanggung jawab sosial adalah program pengembangan masyarakat yang dinilai lebih bermanfaat. System Rice Intensification Organic atau SRI Organik adalah salah satu program pengembangan masyarakat yang dikembangkan untuk meningkatkan kesejahteraan petani. Tujuan dari penelitian ini adalah 1) mengevaluasi dampak yang diberikan SRI Organik sebagai program pengembangan masyarakat; 2) mengukur tingkat pendapatan petani SRI Organik; 3) menganalisis peluang SRI Organik dimasa depan sebagai program yang mandiri dan berkelanjutan. Dengan melakukan studi kasus kepada program pengembangan masyarakat yang dilakukan PT Medco E&P Indonesia pada dusun Parit 9 kab. Banyuasin, penulis melakukan analisis dan evaluasi dampak dengan menggunakan SEAGA terhadap 20 responden. Hasil dari penelitian tersebut dimaksudkan untuk memberikan masukan agar menjadikan program pengembangan masyarakat yang lebih efektif di masa depan. Kata kunci: kesejahteraan, tanggung jawab sosial, pengembangan masyarakat, SRI organik, SEAGA